“Humanization of Algorithms”: Introductio - Gruchoła, Małgorzata (Roczniki Kulturoznawcze, 2024)
Technical progress usurps the title of a kind of architect of the humanization of algorithms and artificial intelligence. More and more often, he proposes substitutes that reality cannot cope with. The intensive development of AI technology, combined with its more frequent use, is changing its status and perception. From a human creation – i.e. a tool, an object – it takes the form of a “social entity”. Generative technologies, chatbots, social robots, by inviting interaction, imply a substitute for communication, “humanizing” the technological interlocutor. The development of information and generative technologies, implying the creation of increasingly complex and independent algorithms and humanoid robots, contributes not only to changing people’s reactions and attitudes towards them, but also to the transformation of the communication process itself. Giving embodied artificial intelligence autonomy of action and the status of a subject of social life may lead, on the one hand, to the dehumanization of communication, and, on the other hand, to the humanization of algorithms, chatbots and robots. The aim of the article was to demonstrate the impact of attributing personal characteristics to algorithms and artificial intelligence – human products – on the dehumanization of the human person and communication. The article is analytical and descriptive in nature.